2022
DOI: 10.1007/s11468-022-01712-w
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Level Instability of Transverse Excitation in Electron Flow

Abstract: In current research we use the effective Schrödinger-Poisson model to study a new kind of quantum level instability in an infinite-wall slab electron system. We use the Madelung fluid representation along with the conventional eigenvalue problem techniques in order to solve the linearized coupled differential equations representing the transverse collective linear excitations in the electron gas of arbitrary degree of degeneracy having a constant perpendicular momentum. It is shown that the energy levels of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…This is a very simplifying assumption which can lead to deviations from real experimental data because of ignorance of electrostatic interactions among electrons which can fundamentally modify the energy dispersion of electrons in collective excitations like plasmons. More recently, a dual length-scale theory of collective electron excitations [55][56][57] has been developed in which the plasmons carry two characteristic momentum, one due to the single-electron oscillations and the other due to their collective electrostatic interaction in the electron gas. It has been shown that the heat capacity of a quantum electron gas is greatly modified due to plasmonic effects at high electron gas temperatures [58].…”
Section: Introductionmentioning
confidence: 99%
“…This is a very simplifying assumption which can lead to deviations from real experimental data because of ignorance of electrostatic interactions among electrons which can fundamentally modify the energy dispersion of electrons in collective excitations like plasmons. More recently, a dual length-scale theory of collective electron excitations [55][56][57] has been developed in which the plasmons carry two characteristic momentum, one due to the single-electron oscillations and the other due to their collective electrostatic interaction in the electron gas. It has been shown that the heat capacity of a quantum electron gas is greatly modified due to plasmonic effects at high electron gas temperatures [58].…”
Section: Introductionmentioning
confidence: 99%